Effectiveness of COVID-19 vaccines against SARS-CoV-2 Omicron variants during two outbreaks from March to May 2022 in Quzhou, China - Zhiying Yin; Quanjun Fang; Tingcui Wen; Canjie Zheng; Canya Fu; Shuangqing Wang; Junji Li; Xiaoying Gong (Taylor & Francis Group, 2023)
Limited data are available on the effectiveness of COVID-19 vaccines used in China in real-world outbreaks - especially against Omicron variants in vaccinated individuals. Two outbreaks of SARS-CoV-2 Omicron variants - the first involving the sub-lineage BA.2 and the second the BA.1 variant - occurred in Quzhou. Infected people and their close contacts were divided according to vaccination status: unvaccinated, partially vaccinated, fully vaccinated, and boosted. The Cox proportional-hazard regression model was used to estimate the evolving hazard for vaccinated individuals after their first immunization. 138 people had been infected with the SARS-CoV-2 Omicron BA.2 variant and 13 with the BA.1 variant. Of the 151 infections, 99.34% (150/151) were mild or asymptomatic and 90.07% (136/151) were vaccine breakthrough cases. The total vaccine effectiveness (VE) of partial, full, and booster vaccinations during the two outbreaks was 47.4% (95%CI: 0-93.1%), 28.9% (95%CI: 0-60.2%), and 27.5% (95%CI: 0-58.3%). The VE of booster vaccination against the Omicron BA.1 variant was higher than that for the BA.2 variant. The cumulative hazard began to increase 220 days after the first immunization. The transmissibility of the Omicron BA.2 variant as for BA.1 did not increase in vaccinated individuals; booster vaccination after a primary course substantially increased protection. Our study found that the SARS-CoV-2 Omicron variant caused less severe illness and that the VE of boosters against the Omicron variant was less than 30%. Timely administration of the booster dose was important, especially for individuals aged over 80 years old.